2009
DOI: 10.1002/adsc.200900438
|View full text |Cite
|
Sign up to set email alerts
|

First Copper‐Catalyzed Intramolecular Amidation in Substituted 4‐Iodopyrazoles Leading to the Synthesis of Pyrazolo[4,3‐b]‐ pyridin‐5‐ones

Abstract: An unprecedented copper-catalyzed intramolecular amidation of substituted 4-iodopyrazoles generated either via Baylis-Hillman or Horner-Wadsworth-Emmons chemistry for the synthesis of pyrazoloA C H T U N G T R E N N U N G [4,3-b]pyridine-5-ones is described. In addition, the effect of the stereochemistry of the acrylamide on the cross-coupling reaction has been investigated and it is demonstrated that only the Z-isomer is favoured to undergo the intramolecular cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…An intramolecular C‐N bond formation of various substituted 4‐iodopyrazoles 17 toward construction of pyrazolo[4,3‐ b ]pyridine‐5‐ones 22 has been reported under the catalysis of CuI. [ 36 ] Firstly, the reaction of 4‐iodopyrazole‐3‐carbaldehydes 17 with acrylonitrile in presence of DABCO yielded the MBH adducts 18 , which upon acetylation followed by S N 2‐displacement with NaBH 4 and controlled hydrolysis with TFA/H 2 SO 4 produced the pyrazole linked amides 21 . Thereafter, the cyclized products, pyrazolo[4,3‐ b ]pyridine‐5‐ones 22 were obtained in 32%‐39% yields via Cu assisted intramolecular C‐N coupling reaction.…”
Section: Copper‐catalyzed Approaches For the Synthesis Of Pyrazole Fumentioning
confidence: 99%
“…An intramolecular C‐N bond formation of various substituted 4‐iodopyrazoles 17 toward construction of pyrazolo[4,3‐ b ]pyridine‐5‐ones 22 has been reported under the catalysis of CuI. [ 36 ] Firstly, the reaction of 4‐iodopyrazole‐3‐carbaldehydes 17 with acrylonitrile in presence of DABCO yielded the MBH adducts 18 , which upon acetylation followed by S N 2‐displacement with NaBH 4 and controlled hydrolysis with TFA/H 2 SO 4 produced the pyrazole linked amides 21 . Thereafter, the cyclized products, pyrazolo[4,3‐ b ]pyridine‐5‐ones 22 were obtained in 32%‐39% yields via Cu assisted intramolecular C‐N coupling reaction.…”
Section: Copper‐catalyzed Approaches For the Synthesis Of Pyrazole Fumentioning
confidence: 99%
“…[3][4][5] 4-Iodo-1,5-diphenyl-1H-pyrazole-3-carbaldehyde and acetamidine hydrochloride were selected as model substrates to optimize the reaction conditions, including optimization of the copper source, ligands, base, and solvents under a nitrogen atmosphere. As delineated in Table 1, four ligands were investigated at 90°C using 10 mol-% CuI as catalyst and 300 mol-% Cs 2 CO 3 as base in dimethyl sulfoxide (DMSO) ( Table 1, entries 2-5); it was found that l-proline (20 mol-%) displayed the best activity.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we have demonstrated that amides derived from the Morita-Baylis-Hillman (MBH) adducts of 4-iodopyrazolecarbaldehyde undergo copper-catalyzed intramolecular Goldberg-type C-N coupling to afford substituted pyrazolo [4,3-b]pyridin-5-ones, whereas the allylamines obtained from the MBH adducts undergo Ullman-type C-N coupling to afford substituted pyrazolo [4,3-b]pyridines. [3,4] In addition, we success-fully synthesized pyrazolo-fused benzodiazepines and benzoxazoazepines through copper-mediated C-N and C-O cross-coupling cascade reactions of 4-iodopyrazolecarbaldehydes with 1,2-phenylenediamines and 2-aminophenols, respectively. [5] However, interestingly, during the study we discovered that only intramolecular C-N and C-O couplings could be performed; the intermolecular version resulted in failure.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recently, we reported the synthesis of pyrazoloA C H T U N G T R E N N U N G [4,3-b]pyridine-5-ones via the first copper-promoted intramolecular amidation in 4-iodopyrazole derivatives generated either from Morita-Baylis-Hillman (MBH) or HornerWadsworth-Emmon chemistry. [5] Although during this study the C À N coupling with allylamides was successful, we failed to achieve similar cross-coupling reactions with allylamines accessed via MBH chemistry. Nevertheless, we were keen to explore the copperpromoted cross-coupling of substituted 4-iodopyrazoles as it would allow access to intermediates suitable for generating novel annulated pyrazoles.…”
mentioning
confidence: 92%